Toxicity of the organophosphate insecticide sumithion to embryo and larvae of zebrafish - Mohammad Shadiqur Rahman; S M Majharul Islam; Anamul Haque; Md. Shahjahan (Toxicology Reports, 2020)
Sumithion, a synthetic organophosphate, is widely used as an agricultural insecticide and for control of tiger bug (Cicindela spp.) in larval rearing for aquaculture. An experiment was conducted to examine the effects of sumithion on embryological and larval development of zebrafish Danio rerio. Fertilized egg (n = 100) and larvae (n = 100) were exposed to six concentrations of sumithion (0, 0.1, 0.2, 0.4, 0.8 and 1.6 mg L−1) in three replicates. LC50 values for embryos and larvae were calculated by probit analysis. The 24 h LC50 value of sumithion for embryo was 0.235 (0.079-0.428) mgL−1. Increasing sumithion concentrations decreased hatching success and increased embryonic mortality. In embryos, sumithion induced several malformations including immature yolk sac, dark yolk sac, yolk sac bud, broken eggshell and notochord, unhatched eggs. Larval LC50 values at 24, 48 and 72 h of various doses of sumithion exposure were 0.620 (0.436-0.963), 0.475 (0.302-0.801) and 0.341 (0.177-0.617) mgL−1, respectively. Various physical deformities, including edema, notochord deformity, yolk sac damage, body arcuation, lordosis and black pigmentation on the yolk sac were evident in response to different concentrations of sumithion. The results of the current study indicate that sumithion exerts developmental toxicity to zebrafish embryos and larvae. It is expected that current findings will increase sensitivity about the toxic effect of sumithion in early development, as well the possibility of similar actions induced by other insecticides and pesticides.